Modeling the Empowerment Mechanism of Knowledge Collaboration from the Perspective of Platform Affordances - Zeyu Jiao; Jianbin Chen (Discrete Dynamics in Nature and Society)
In the digital economy era, knowledge platforms have both the functions of knowledge collaboration and social media. At the same time, how to promote knowledge collaboration through platform empowerment is getting more and more attention. Since there are few types of research on how to realize the micromechanism of platform empowerment, the purpose of this paper is to take knowledge platforms as an example to study the conceptual system of platform affordances based on the social-technical perspective. Through the theoretical integration of technological empowerment and authorization empowerment, this paper provides new perspectives and future themes for explaining the platform empowerment mechanism of knowledge collaboration. As for the method, the deductive research approach is adopted in this paper. First, through the critical literature review, the gaps in platform empowerment research have been identified. Second, from the analysis of the characteristics of knowledge platforms such as Wukong Q&A and Zhihu, the relationship between platform affordances, platform organizational characteristics, and customer needs has been explored. In the final, according to knowledge platform characteristics, the conceptual system of platform affordances has been deduced. The result shows that through integrating organizational theory, knowledge management theory, and platform ecological viewpoints, the main components of the affordances of knowledge platforms have been summarized. In addition, the relevance of those components to the functions, interfaces and rules of the platform system has been illustrated, and the corresponding relationship between the affordances of the platform and the main components of authorization empowerment has been established. With regard to the implication of this study, it establishes the theoretical connection between technological empowerment and authorization empowerment and provides a more intuitive and operable method for platform empowerment of knowledge collaboration through the perspective of social-technical interaction. This paper emphasizes that starting from the mission of the platform, the stickiness of the platform can be enhanced by building platform affordances. In addition, extensive development ideas that purely pursue Internet traffic and capital need to be avoided, which is conducive to the high-quality development of knowledge platforms and the digital economy. Furthermore, this paper calls for more research on the affordances and empowerment mechanism of the platform to provide theoretical guidance for the highly unified practice of platform organizational characteristics, platform system characteristics, and target customer needs, so as to develop a more active and meaningful platform knowledge management field.